2024
DOI: 10.1002/jmv.29416
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody response after immunization with a COVID‐19 bivalent vaccine: Insights to the future

Milena Silva Souza,
Jéssica Pires Farias,
Robert Andreata‐Santos
et al.

Abstract: The raising of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants led to the use of COVID‐19 bivalent vaccines, which include antigens of the wild‐type (WT) virus, and of the Omicron strain. In this study, we aimed to evaluate the impact of bivalent vaccination on the neutralizing antibody (NAb) response. We enrolled 93 volunteers who had received three or four doses of monovalent vaccines based on the original virus (n = 61), or a booster shot with the bivalent vaccine (n = 32). Serum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Across a diverse set of participants, we found evidence for a statistically significant increase in antibodies specific for both SARS-CoV-2 variants after a single dose of the bivalent boost, although the response to the Wuhan-Hu-1 variant was much stronger than response to the Omicron BA.4/BA.5 variant at all timepoints. This supports the findings of previous studies that a single dose of this bivalent booster does not produce a strong antibody response specific to the Omicron BA.4/BA.5 spike protein (5)(6)(7)(8)(9). Our data from the DBS ELISA, DBS neutralization assays, as well as saliva ELISAs were consistent and revealed that the Wuhan-Hu-1 antibody response dwarfed the Omicron BA.4/BA.5-specific response in this population before the boost, at all timepoints after the boost, and in individuals who became infected after receiving the bivalent boost.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Across a diverse set of participants, we found evidence for a statistically significant increase in antibodies specific for both SARS-CoV-2 variants after a single dose of the bivalent boost, although the response to the Wuhan-Hu-1 variant was much stronger than response to the Omicron BA.4/BA.5 variant at all timepoints. This supports the findings of previous studies that a single dose of this bivalent booster does not produce a strong antibody response specific to the Omicron BA.4/BA.5 spike protein (5)(6)(7)(8)(9). Our data from the DBS ELISA, DBS neutralization assays, as well as saliva ELISAs were consistent and revealed that the Wuhan-Hu-1 antibody response dwarfed the Omicron BA.4/BA.5-specific response in this population before the boost, at all timepoints after the boost, and in individuals who became infected after receiving the bivalent boost.…”
Section: Discussionsupporting
confidence: 91%
“…These updated vaccines contain mRNA for both the original Wuhan-Hu-1 and the Omicron BA.4/BA.5 variants and were approved by the FDA in August of 2022 1 , 2 . Preliminary studies indicated that the effectiveness of bivalent boosters was higher than that of original monovalent boosters at decreasing incidences of severe COVID-19 (1), but several subsequent studies reported that the antibody response resulting after the bivalent boost is not specific to the newer variants (2)(3)(4)(5)(6). Given that this bivalent boost was approved in late 2022, the IgG response to this bivalent booster over an extended period is largely unstudied.…”
Section: Introductionmentioning
confidence: 99%